Stoichiometric control for heteroepitaxial growth of smooth ε-Ga2O3 thin films on c-plane AlN templates by mist chemical vapor deposition. (22nd June 2017) - Tahara, Daisuke; Nishinaka, Hiroyuki; Morimoto, Shota; Yoshimoto, Masahiro
Abstract: Epitaxial ε-Ga2 O3 thin films with smooth surfaces were successfully grown on c -plane AlN templates by mist chemical vapor deposition. Using X-ray diffraction 2θ–ω and ϕ scans, the out-of-plane and in-plane epitaxial relationship was determined to be (0001) ε-Ga2 O3 ∥ (0001)AlN . The gallium/oxygen ratio was controlled by varying the gallium precursor concentration in the solution. While scanning electron microscopy showed the presence of large grains on the surfaces of the films formed for low concentrations of oxygen species, no large grains were observed under stoichiometric conditions. Cathodoluminescence measurements showed a deep-level emission ranging from 1.55–3.7 eV; however, no band-edge emission was observed.